Grappling with the Bomb Britain's Pacific H-bomb tests - Maclellan, Nic (Pacific Series, 2017)
Grappling with the Bomb is a history of Britain's 1950s program to test the hydrogen bomb, code name Operation Grapple. In 1957-58, nine atmospheric nuclear tests were held at Malden Island and Christmas Island-today, part of the Pacific nation of Kiribati. Nearly 14,000 troops travelled to the central Pacific for the UK nuclear testing program-many are still living with the health and environmental consequences. Based on archival research and interviews with nuclear survivors, Grappling with the Bomb presents i-Kiribati woman Sui Kiritome, British pacifist Harold Steele, businessman James Burns, Fijian sailor Paul Ah Poy, English volunteers Mary and Billie Burgess and many other witnesses to Britain's nuclear folly.